3D CT data segmentation/ Lai Chew Ping - Lai , Chew Ping (2005)
The purpose of this project is to explore, understand and utilize a three- dimensional (3D) Visualization and segmentation software to perform segmentation on 3D Computed tomography (CT) data sets. The software selected in this project is Amira developer version 3.0 A step by step guide on how segmentation is done using Amira is shown.This report contains six chapters which uncovered the details of the project from the initial planning to analysis and design as well as implementation at the end of the project. It includes the selection of development tools, methodology, system requirements and hierarchy. Finally, the discussions on problems encountered and recommended solutions, system strength and limitation, future enhancements and conclusion are provided.